Peran Moderasi Corporate Governance dalam Hubungan Koneksi Politik, Kompensasi Bonus dan Manajemen Laba - Maharti, Wise; Nugrahanti, Yeterina Widi (E-Jurnal Akuntansi; Vol 32 No 7 (2022), 2022)
The research objectives are to examine the effect of political connections and bonus compensation on earnings management, and to examine the role of corporate governance in the influence of political connections and bonus compensation on earnings management. The study was conducted on manufacturing companies listed on the IDX from 2016-2020 and this study used quantitative data analysis methods with Moderating Regression Analysis (MRA) as hypothesis testing. The results of the research on political connections and bonus compensation have an effect on earnings management. Independent commissioners can weaken the positive influence of political connections on earnings management, while institutional ownership and audit quality have no effect on earnings management. In addition, independent commissioners and institutional ownership cannot weaken the positive effect of bonus compensation on earnings management, but audit quality can actually weaken this effect. Keywords: Earnings Management; Political Connections; Bonus Compensation; Corporate Governance; Independent Commissioners; Institutional Ownership; Audit Quality.